Observation and mass measurement of the baryon Ξb- - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We report the observation and measurement of the mass of the bottom, strange baryon Ξb- through the decay chain Ξb-→J/ψΞ-, where J/ψ→μ+μ-, Ξ-→Λπ-, and Λ→pπ-. A signal is observed whose probability of arising from a background fluctuation is 6.6×10-15, or 7.7 Gaussian standard deviations. The Ξb- mass is measured to be 5792.9±2.5(stat) ±1.7(syst)MeV/c2. © 2007 The American Physical Society.